Cystatin-C marker in diabetic and non diabetic patients with ischemic heart disease - Mutlak, Shaimaa S.; Turki, Kismat M.; Saeed, Basil N. (Journal of the Faculty of Medicine Baghdad, 2012)
Background:recent data indicate the prevalence of cardiovascular disease in patientswith high cystatin-C level;it can be used as a good predictor for assessment of mortality in cardiovascular diseases regardless of the status of renal function. Patients and methods: Onehundred twenty (120) patients with ischemic heart disease admitted to this study at Baghdad teaching hospital for the period from January 2011 to September2011,Those patients categorized into two groups (60) diabetic and (60) non diabetic in comparison to fifty healthy control.Fasting serum cystatin-C was measured in all patients and controls. Results: The level of serum cystatin-C, in diabetic patients with ischemic heart disease was (2.05±0.55 μg/L). Its level in non diabetic patients with ischemic heart disease was (1.19±0.59 μg/L)both were significantly higher(p<0.001)than its level in healthy control(0.38±0.062 μg/L). Conclusion:Cystatin-C is good prognostic biomarker in patients with ischemic heart disease with or without diabetes mellitus.